Auf wiedersehen coronary stenosis? Not so fast mein Herr. Issue 5 (9th November 2021) - Wani, Omar; Butman, Samuel M.
Key Points: The present analysis is a real‐world angiographic data report on EES‐implantation for the treatment of ISR. The report demonstrates comparable results to randomized prospective trials regarding the efficacy of treating ISR with EES. Real world analyses, while not as definitive as prospective trials, are nonetheless reassuring given a typically more diverse and inclusive cohort. Treatment with a drug‐eluting stent for ISR remains the first treatment of choice, for now, at least.